Analysis of Vitamin C (ascorbic acid) Contents in Various Fruits and Vegetables by UV-spectrophotometry (Bangladesh Journal of Scientific and Industrial Research, 2008)
Total vitamin C (ascorbic acid + dehydroascorbic acid) has been determined by UVspectrophotometric method in various fruits and vegetables. In this method bromine water oxidizes ascorbic acid to dehydroascorbic acid in presence of acetic acid. After coupling with 2,4-dinitrophenyl hydrazine at 37&deg:C temperature for three hours, the solution is treated with 85% H2SO4 to produce a red color complex and the absorbance was spectrophotometrically measured at 521 nm. The content of vitamin C were 10 mg/100g to 80 mg/100g in fruits and 16 mg/100g to 42 mg/100g in vegetables. Aloss of 64% at -10°C and 76% at 5°C was observed after two months storage period of one leafy vegetable "Enhydra fluctuans" (Helencha shak). Key words: Vitamin C determination, Vegetables, Fruits, UV-spectrophotometer.